Factors associated with the development of dynapenia in patients with ulcerative colitis - G. R. Bikbavova; M. A. Livzan; N. S. Lisyutenko; A. E. Romanyuk; A. A. Bondarenko (Бюллетень сибирской медицины)
Aim. To evaluate the association of insulin resistance and secretion of neuropeptide Y with dynapenia in patients with ulcerative colitis (UC). Materials and methods. A single-center observational cross-sectional study included 80 patients with UC. Participants were divided into two groups: patients with dynapenia and patients with normal hand grip strength. The body mass index (BMI), dietary habits and stress levels were studied, patients underwent dynamometry. C-reactive protein (CRP), TNF-α, interleukin-6, leptin, adiponectin, soluble leptin receptors (sOb-R), neuropeptide Y and peptide YY, insulin and glucose were measured in blood serum. We determined the index of insulin resistance HOMA-IR. Median (Me) of the upper and lower quartiles (P25; P75), proportion and standard error of the proportion were calculated. We also determined the Mann-Whitney and Kruskal-Wallis tests, Yates chi-squared test, and twotailed Fischer’s test. The Spearman’s correlation coefficient was calculated. Results. 54 ± 5.6% of patients with dynapenia were overweight or obese. It should be noted that patients with dynapenia were relatively young (35 (32; 51) years). Dynapenia is associated with increased CRP levels, insulin resistance, and higher values of neuropeptide Y. We found a positive correlation between neuropeptide Y and the consumption of simple carbohydrates and alcoholic beverages. The study did not reveal relationship between the concentration of neuropetide Y and the activity of UC, the localization of the pathological process, and the course of the disease. A positive association between neuropeptide Y and the level of sOb-R, peptide YY, was established. Conclusion. Long-lasting chronic inflammation leads to the premature development of dynapenia and insulin resistance in patients with UC at a young age. In patients with dynapenia, the level of neuropeptide Y is significantly higher than in patients without dynapenia, which is probably due to the regulation of energy balance, glucose and insulin homeostasis.